Comparison of methods for estimating basal endogenous losses of amino acids and additivity of digestibility of amino acids in corn and soybean meal for broilers - June Hyeok Yoon; Changsu Kong (Animal Nutrition, 2023)
This study was to compare the estimates of basal endogenous losses (BEL) of amino acids (AA) determined by 3 methods including feeding a nitrogen-free diet (NFD) or a low-casein diet (LCD, containing casein at 30 g/kg diet) or using the regression method. Another objective was to investigate whether the ileal AA digestibility of corn calculated from a casein-supplemented corn diet is additive for a corn-soybean meal (SBM) mixed diet in broilers. On d 31 of age, 168 Ross 308 male broilers were assigned to 8 dietary treatments with 6 replicates in a randomized complete block design. An NFD and 3 diets containing 30, 60, or 90 g/kg of casein were formulated to determine the BEL of AA and ileal AA digestibility of casein. The other 4 diets consisted of a corn diet, SBM diet, casein-supplemented corn diet, and corn-SBM mixed diet. On d 35 of age, digesta from the distal section of the ileum were collected. The BEL of AA in birds fed the LCD were greater (P < 0.05) than those of the NFD and the regression method. There were no differences in the BEL of AA determined between the NFD and the regression method. Apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of AA for corn calculated from the casein-supplemented corn diet were greater (P < 0.05) than those of the corn diet. The predicted AID of Thr in the corn-SBM mixed diet based on the AID of AA for corn in the corn diet was lower (P < 0.05) than the measured AID. However, the predicted AID of AA in the mixed diet based on the AID of AA for corn in the casein-supplemented corn diet did not differ from the measured AID. The predicted SID of AA in the mixed diet did not differ from the measured SID irrespective of casein supplementation. In conclusion, feeding an NFD or using the regression method yields similar BEL of AA, but not feeding an LCD. Casein supplementation in the corn diet increases the ileal AA digestibility for corn, which is additive for the corn-SBM mixed diet.